Healthcare chauvinism during the COVID-19 pandemic. Issue 7 (19th May 2021) - Haderup Larsen, Mikkel; Schaeffer, Merlin
ABSTRACT: Social science research has produced evidence of welfare chauvinism whereby citizens turn against social policies that disproportionately benefit immigrants and their descendants. Some policymakers advocate welfare chauvinism as a means to incentivize fast labour market integration and assimilation into the mainstream more generally. These contested arguments about integration incentives can hardly be extended to the case of hospital treatment of an acute COVID-19 infection. On that premise we conducted a pre-registered online survey experiment among a representative sample of the Danish population about healthcare chauvinism against recent immigrants and Muslim minorities during the peak of the COVID-19 pandemic of spring 2020. Our results show no evidence of blatant racism-driven healthcare chauvinism against acute COVID-19 patients with a Muslim name who were born in Denmark. However, we do find evidence of healthcare chauvinism against patients with a Danish/Nordic name who immigrated to Denmark only a year ago. Moreover, healthcare chauvinism against recently-immigrated COVID-19 patients doubles in strength if they have a Muslim name. Our findings thus suggest that there is general reciprocity-motivated welfare chauvinism against recent immigrants who have not contributed to the welfare state for long and that racism against Muslims strongly catalyses this form of welfare chauvinism.